A 3‐day low‐fibre diet does not improve colonoscopy preparation results compared to a 1‐day diet: A randomized, single‐blind, controlled trial. Issue 10 (1st December 2019) - Taveira, Filipe; Areia, Miguel; Elvas, Luís; Alves, Susana; Brito, Daniel; Saraiva, Sandra; Cadime, Ana T
Abstract : Background: Although a 1‐day low‐fibre diet before colonoscopy is currently recommended, some endoscopists prescribe a 3‐day diet. Objective: The objective of this study was to compare the influence of a 3‐day versus a 1‐day low‐fibre diet on bowel preparation quality, patient tolerability and adherence. Methods: Outpatients scheduled for total colonoscopy were randomized in two groups, 3‐day versus 1‐day low‐fibre diet, performing a 4‐litre polyethylene glycol split‐dose. The primary outcome was a reduction of inappropriate preparations in the 3‐day low‐fibre diet arm from 15% to 5% (bowel preparation was assessed by the Boston Bowel Preparation Scale). Secondary outcomes were adherence to, difficulty to perform, difficulty to obtain and willingness to repeat the diet. Intention‐to‐treat (ITT) and per‐protocol (PP) analyses were conducted for the primary outcome. Results: A total of 412 patients were randomized (206 per group). Bowel preparation quality was similar between groups. On ITT analysis ( n = 412), adequate bowel preparation was 91.7% (3‐day diet) versus 94.7% (1‐day diet), p = 0.24 and on PP analysis ( n = 400) 93.5% versus 96.5%, respectively, p = 0.16. Difficulty to perform the diet was significantly higher on the 3‐day diet, p = 0.04. No differences were found on difficulty to obtain the diet, willingness to repeat the diet, adverse events and intra‐colonoscopy findings. Conclusion: A 3‐day low‐fibre diet does not bring benefit to the bowel preparation quality and is harder to perform than a 1‐day diet.